Audiometric Outcome Comparison between Titanium Prosthesis and Molded Autologous Material. (August 2014) - Órfão, Tiago; Júlio, Sara; Ramos, José Filipe; Dias, Cláudia Camila; Silveira, Helena; Santos, Margarida
Objective: To evaluate and compare the audiometric outcomes of ossicular reconstruction with titanium prosthesis and autologous material. Study Design: Retrospective cohort study. Setting: Tertiary referral center. Subjects and Methods: Audiometric results of consecutive patients who performed ossiculoplasty with titanium prosthesis (n = 43) or autologous material (n = 48), from October 2008 to December 2011, were reviewed retrospectively and compared. The association between air-bone gain and age, ossiculoplasty material (autologous or titanium), preoperative diagnosis (chronic otitis media without cholesteatoma, cholesteatoma, or conductive hearing loss with intact tympanic membrane), and type of surgery (tympanoplasty, canal wall-down mastoidectomy, or canal wall-up mastoidectomy) was explored using regression analysis. Results: Preoperative audiometric evaluation did not show differences between titanium and autologous groups in air-bone gap and pure-tone average. A postoperative decrease of 11.0 dB in air-bone gap and 12.4 dB in pure-tone average was observed in titanium ossiculoplasty compared with a reduction of 4.0 dB in air-bone gap and 5.1 dB in pure-tone average when autologous reconstruction was used. Mann-Whitney test revealed superior results in the titanium group compared with autologous reconstruction patients in air-bone gap ( P = .02) and pure-tone average ( P = .02). However, no statistically significant associations were observed after multivariate linear regression analysis of air-bone gap gain when adjusted for age, ossiculoplasty material, type of surgery, and preoperative diagnosis. One titanium prosthesis extrusion occurred during follow-up (2%). Conclusion: Audiometric results achieved by titanium prosthesis are promising, but significant differences compared with autologous ossiculoplasty were not present.